Dietary hydrogenated fat increases high-density lipoprotein apoA-I catabolism and decreases low-density lipoprotein apoB-100 catabolism in hypercholesterolemic women - Matthan, Nirupa R; Welty, Francine K; Barrett, P Hugh R; Harausz, Carrie; Dolnikowski, Gregory G; Parks, John S; Eckel, Robert H; Schaefer, Ernst J; Lichtenstein, Alice H (Arteriosclerosis, thrombosis, and vascular biology, 2004)
To determine mechanisms contributing to decreased high-density lipoprotein cholesterol (HDL-C) and increased low-density lipoprotein cholesterol (LDL-C) concentrations associated with hydrogenated fat intake, kinetic studies of apoA-I, apoB-100, and apoB-48 were conducted using stable isotopes. Eight postmenopausal hypercholesterolemic women were provided in random order with 3 diets for 5-week periods. Two-thirds of the fat was soybean oil (unsaturated fat), stick margarine (hydrogenated fat), or butter (saturated fat). Total and LDL-C levels were highest after the saturated diet (P<0.05; saturated versus unsaturated) whereas HDL-C levels were lowest after the hydrogenated diet (P<0.05; hydrogenated versus saturated). Plasma apoA-I levels and pool size (PS) were lower, whereas apoA-I fractional catabolic rate (FCR) was higher after the hydrogenated relative to the saturated diet (P<0.05). LDL apoB-100 levels and PS were significantly higher, whereas LDL apoB-100 FCR was lower with the saturated and hydrogenated relative to the unsaturated diet. There was no significant difference among diets in apoA-I or B-100 production rates or apoB-48 kinetic parameters. HDL-C concentrations were negatively associated with apoA-I FCR (r=-0.56, P=0.03) and LDL-C concentrations were negatively correlated with LDL apoB-100 FCR (r=-0.48, P=0.05). The mechanism for the adverse lipoprotein profile observed with hydrogenated fat intake is determined in part by increased apoA-I and decreased LDL apoB-100 catabolism.